Measurement Properties for a Scale Assessing Self-Regulation in Parents and Parenting Practitioners. - Tellegen, Cassandra L.; Ma, Tianyi; Day, Jamin J.; Hodges, Julie; Panahi, Babak; Mazzucchelli, Trevor G.; Sanders, Matthew R. (Journal of Child & Family Studies, 2022)
Parenting self-regulation is increasingly recognised as an important facet of positive parenting, as it allows parents to manage their thoughts, behaviours, emotions and attention in order to effectively carry out parenting tasks. Evidence-based parenting programmes such as the Triple P-Positive Parenting Program aim to increase parenting self-regulation by teaching parents a range of skills and strategies to deal with everyday parenting. Despite the importance of self-regulation within the field of parenting, few measures assessing this construct are available. The current investigation aims to add to existing literature by evaluating the measurement properties of a brief and parsimonious measure of self-regulation for both parents and parenting practitioners, the Parenting Self-Regulation Scales (PSRS)—Parent and Practitioner versions. Exploratory and Confirmatory Factor Analyses gave support for a single-factor model for the parent version, and this was confirmed in the practitioner version. Both versions demonstrated excellent internal consistency and hypothesis testing supported the construct validity of both scales. The results indicate that the PSRS is a promising brief measure of parenting self-regulation for parents and practitioners which could prove useful to both clinical work and research in the parenting field. Highlights: Evaluated measurement properties of a 12-item brief measure of self-regulation for parents and practitioners delivering parenting programmes. Factor analyses supported a single-factor structure, and both scales displayed excellent internal consistency. Parent version can be used with parents to assess parental self-regulation in parenting. Practitioner version can be used to assess practitioners' self-regulation in delivering parenting programmes. Both versions of the measure displayed convergent and concurrent validity for use with the targeted populations.